Cases of motion for reconsideration of Kuwaiti law - Aljefairi, Ali Hasan (Journal of Economic, Administrative and Legal Sciences, 2022)
This research dealt with the cases in which a motion for reconsideration may be submitted in accordance with the Kuwaiti Civil and Commercial Procedures Law, and the Law of Procedure and Criminal TrialsThe research contains definition of reconsideration, how its important, and mentioned the cases which are six cases: the case of fraud, the case of forgery, case of appears new evidence, the case of the judgment exceeding the limits of the requests, the case of contradiction of the judgment uttered, and the case of lack of proper legal representation.The research included defining each of these cases, distinguishing them from what may be similar, and clarifying the conditions that must be considered, as well as mentioning some pictures and examples related to each case, with a controlled expansion to obtain a comprehensive vision of the retrial cases, the researcher use inductive and Comparative method.The study concluded with the importance of reconsideration and the recent legislation of the legislative authority in Kuwait in the Code of Procedures and Criminal Trials.
Keywords: judgments; appeal; judiciary; review; trial